Catalogue of books printed before 1801 in the legal historical section of the Biblioteca di Scienze Sociali dell'Università degli Studi di Firenze I. From the beginning of printing to 1600 - Douglas J. Osler (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2014)
The present catalogue is the first of three volumes which record the books printed before 1801 currently held by the legal historical section of the Biblioteca di Scienze Sociali of the Università degli Studi di Firenze. This volume encompasses 1,532 editions published from the beginning of printing to 1600. The present Florence library is the successor to that of the Facoltà di Giurisprudenza, the nucleus of which is the historic collection of the Collegio degli Avvocati di Firenze acquired in 1924. Supplemented by further important acquisitions, including the library of the Corte d'Appello, the collection has come to be numbered among the foremost in its field in Italy. The 16th century volume exhibits a wide range not only of the famous medieval authors of the ius commune, but also of the growing number of contemporary 16th century jurists.